Surgical suture and method of making same
Patent Information
- Application Number
- CN202311250100.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-09-26
AI Technical Summary
但是,将壳聚糖、丝素蛋白与聚乳酸混纺会导致静电纺纤维的力学性能降低;并且,由于聚乳酸的降解速率慢,导致药物缓释效果差、难以调控;还存在手术缝合线在使用过程中不滑脱退让,壳聚糖、丝素蛋白和负载药物同时释放,难以在伤口愈合的不同阶段发挥作用等问题
[0023](1)具备优良的力学性能。利用同轴共轭静电纺丝技术制备具有皮芯结构的多孔载药纳米纤维功能包裹层包裹力学性能优良的可降解长丝缝合线芯纱层,使本发明包芯纱结构的新型手术缝合线具有优良的力学性能,同时因挥发油的加入,载药纳米纤维直径均匀、表面多孔且粗糙,具有多层次、多维度的孔道连通结构,并表现出无序聚集状态,这种表面形貌可有效的增大纤维表面摩擦力,提高缝合线耐疲劳性和摩擦耐受性等力学性能,使本发明手术缝合线在使用过程中不易滑脱退让,增强其缝合线使用效果。
Smart Images

Figure CN117531037B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of disposable medical surgical consumables, and particularly relates to a surgical suture and its preparation method. Background Technology
[0002] Surgical sutures were among the first commercially available medical textiles, used for wound closure, tissue bonding, and accelerating wound healing, showing great promise in the medical field. Current research both domestically and internationally urgently needs to develop novel sutures with diverse structures and functions to improve their ability to promote wound healing, increase treatment efficiency, and reduce medical costs, making them more suitable for clinical use and bringing greater benefits to patients. To address the problems with current absorbable sutures, researchers have modified them with drug coatings, which has improved their mechanical properties to some extent, but still suffers from limitations such as insufficient drug loading and sustained release. How to effectively improve the drug loading and sustained release performance of absorbable surgical sutures while maintaining their mechanical properties is a pressing issue. Ideal medical sutures require good elasticity, good biocompatibility, antibacterial properties, healing-promoting capabilities, strong cell adsorption capacity, minimal foreign body reaction, and the ability to inhibit bacterial growth at the wound site and induce wound tissue growth.
[0003] With the widespread application and development of electrospinning technology in various fields, it has also begun to shine in tissue engineering and biomedicine. The nanofibers produced by electrospinning possess excellent mechanical properties, high porosity, high specific surface area, light weight, high permeability, and high absorbency, leading to their increasingly widespread application in surgical sutures. Fiber materials prepared by electrospinning exhibit good mechanical strength, and their three-dimensional structure is similar to the microstructure of the extracellular matrix, providing necessary support and guidance for cells, thus promoting cell proliferation and the growth of new tissues. The high porosity allows this material to not only rapidly absorb wound exudate and maintain wound moisture but also provides excellent breathability and prevents the penetration of external microorganisms. The high specific surface area also enables rapid and effective hemostasis. Over the past decade, this technology has been widely used in the preparation of medical dressings.
[0004] Furthermore, wounds can be categorized into acute and chronic wounds based on the time required for healing. Currently, the functions of medical dressings for acute wounds mainly focus on pain relief, hemostasis, and infection control; while chronic wounds are often caused by other diseases, and their healing process is influenced by multiple factors. Therefore, medical dressings for chronic wounds need to accommodate multiple functions. To make wound dressings multifunctional, researchers typically add various loading materials during the electrospinning process. Researchers can add loading materials according to different wound types and different stages of wound healing, thus "customizing" medical dressings for patients.
[0005] Because nanofiber felt prepared by electrospinning technology has poor mechanical properties, it is difficult to use as surgical sutures. Therefore, it is usually prepared into nanofiber yarn. In particular, nanofiber core-spun yarn, by depositing nanofibers on filaments / yarns to form a core layer, provides mechanical support and can load drugs into the outer nanofibers to achieve multiple functions. Therefore, nanofiber core-spun yarn shows broad prospects as a surgical suture. There are also many methods for preparing nanofiber core-spun yarn. For example, patent publication number CN104032423A discloses an apparatus for electrospinning nanofiber core-spun yarn and its application. The apparatus includes a twisting device, an unwinding device, a winding device, a dual-needle electrospinning device, and a control system. This apparatus has high controllability of the arrangement of nanofibers on the surface of the core-spun yarn. Furthermore, patent publication number CN109554794A discloses an electrospinning nanofiber core-spun yarn forming device and method. The device includes a high-voltage power supply, a metal ring, a metal disk, a drive motor, an insulated transmission rod, a spinning injection device, a core yarn unwinding machine, and a winding machine. The metal disk has a through hole at its center and is grounded. The metal ring is also grounded. The spinning injection device includes an injection pump, an infusion tube, and a needle. The needle is inclined on the other side of the metal disk, with its tip facing the metal disk. The negative terminal of the high-voltage power supply is grounded, and the positive terminal is located at the tip of the needle. The high-voltage power supply is used to generate an electric field between the tip of the needle, the metal disk, and the metal ring. The drive motor rotates the metal disk via the insulated transmission rod, causing the oriented nanofibers to be twisted at a certain angle and wrapped around the core yarn. The nanofibers are arranged orderly on the core yarn to form a nanofiber core-spun yarn.
[0006] Patent publication number CN108193342A discloses a method for preparing drug-loaded nanofiber core-spun yarn for absorbable surgical sutures. The method involves adding an antibacterial and anti-inflammatory drug to a hexafluoroisopropanol solution of chitosan, silk fibroin, and polylactic acid, mixing thoroughly to form a spinning precursor solution; using biodegradable surgical sutures as the core yarn; and employing electrospinning to prepare a uniform and continuous drug-loaded nanofiber core-spun yarn. However, blending chitosan, silk fibroin, and polylactic acid leads to a decrease in the mechanical properties of the electrospun fibers; furthermore, the slow degradation rate of polylactic acid results in poor and difficult-to-control sustained-release of the drug; and there are also problems such as the surgical suture not slipping or retracting during use, and the simultaneous release of chitosan, silk fibroin, and the loaded drug, making it difficult to exert their effects at different stages of wound healing.
[0007] Therefore, the preparation of a novel surgical suture with a multifunctional layer structure combining an easily degradable porous structure, a drug sustained-release layer, a healing-promoting peptide layer, a support layer with excellent mechanical properties, and a rough surface area with high water retention and liquid absorption to increase friction and prevent slippage is particularly important. Its preparation process is simple, highly operable, and has good biocompatibility, and has high market application prospects. Summary of the Invention
[0008] To address the technical challenges of surgical sutures, including their mechanical properties, biodegradability, controlled drug release, promotion of tissue cell growth, water retention, and absorbency, this invention proposes a surgical suture and its preparation method. The proposed surgical suture possesses a multifunctional layer structure, including an easily degradable porous structure, a drug sustained-release layer, a healing-promoting polypeptide layer, a support layer with excellent mechanical properties, and a rough surface area layer with high water retention and absorbency to increase friction and prevent slippage. This effectively solves various requirements for an ideal surgical suture.
[0009] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0010] A surgical suture includes a porous drug-loaded nanofiber functional wrapping layer and a core yarn support layer. The porous drug-loaded nanofiber functional wrapping layer includes core-skin structured nanofibers, which include a drug-loaded skin layer and a biomaterial core layer.
[0011] A method for preparing surgical sutures involves using an apparatus for preparing electrospun nanofiber core-spun yarn. The apparatus includes a coaxial electrospinning machine. The preparation method is as follows: (1) mixing a polymer and a drug to prepare a skin spinning solution; (2) dissolving a biomaterial to prepare a core spinning solution; (3) using the skin spinning solution and the core spinning solution via a coaxial electrospinning machine to obtain core-spun nanofibers and wrapping them around the core yarn. After obtaining the surgical sutures, they are placed in a vacuum drying oven and dried for 12-48 hours to remove residual solvent.
[0012] In step (1), a pore-forming agent is also added to the cortex spinning solution. The amount of the pore-forming agent added is 1-3% of the polymer mass. The pore-forming agent is a volatile oil. The volatile oil can be extracted from the fabric. Preferably, the volatile oil is 4-terpineol or dodecaaldehyde.
[0013] The concentration of polymer in the skin spinning solution is 5-15 wt%; the amount of drug added is 1-3% of the polymer mass.
[0014] The polymer is polylactic acid, and the solvent of the skin spinning solution is one or more of hexafluoroisopropanol, chloroform, or acetone; the drug may be one or more of antibiotics, anti-inflammatory drugs, hemostatic drugs, or vitamins.
[0015] The drug in question is either amoxicillin or Bupleurum chinense.
[0016] The concentration of biomaterial in the core spinning solution is 10-20 wt%.
[0017] The biomaterial is one or more of keratin, gelatin, silk protein, collagen, chitosan, or polypeptide; preferably, the biomaterial is zein-frog skin polypeptide; the solvent of the core spinning solution is one or more of hexafluoroisopropanol, chloroform, or acetone.
[0018] The core yarn is one or more of polyglycolic acid, polylactic acid, and polydioxanone sutures.
[0019] The apparatus for preparing electrospun nanofiber core-spun yarn is a coaxial conjugate electrospinning apparatus. The coaxial conjugate electrospinning apparatus further includes a twisting device, an unwinding device, and a winding device. It is equipped with two coaxial electrospinning machines arranged symmetrically. The technical parameters for preparing surgical sutures using the coaxial conjugate electrospinning apparatus are as follows: voltage 18-28kV, stock solution propulsion speed 1-5mL / h, distance between two needles 20-30cm, receiving distance 20-35cm, winding device rotation speed 2-5r / min, twisting device rotation speed 200-400r / min, temperature 20-35℃, and relative humidity around 30-60%.
[0020] The beneficial effects of the present invention are as follows: The surgical suture proposed in this invention has a biodegradable porous structure and a multifunctional layer structure, including a rough surface layer with high water retention and liquid absorption to increase friction and prevent slippage, a drug sustained-release layer, a healing-promoting polypeptide layer, and a support layer with excellent mechanical properties, which can effectively solve various requirements of an ideal surgical suture.
[0021] Mechanical properties are important for the selection of sutures to avoid accidental breakage during use. Compared with the prior art, the present invention selects absorbable yarn with excellent mechanical properties, biodegradability and good biocompatibility as the core yarn layer, which mainly provides the necessary mechanical support. To manufacture high-quality sutures with multifunctional engineering surfaces, this invention employs coaxial conjugate electrospinning technology. Compared to existing technologies, this invention prepares porous drug-loaded nanofibers with a core-skin structure as the functional encapsulation layer of the suture. The prepared nanofibers exhibit a porous core-skin structure with a high specific surface area and a rough surface. The core-skin structure is obtained using a coaxial needle, allowing for efficient drug loading within the core structure and controlled drug release. The porous structure is obtained using volatile oils extracted from plants. The core layer serves as a healing-promoting material, promoting tissue cell growth and enhancing healing ability. In the early stages of bacterial infection, the drug-loaded porous core structure gradually releases drugs to eliminate bacteria and promote tissue cell growth. In the later stages, the polymer raw materials of the porous core structure gradually degrade, also eliminating some bacteria and accelerating wound healing. Furthermore, it has no toxic side effects on normal cells, ensuring good biocompatibility. The core structure contains polypeptides and other cell-growth-promoting materials, further accelerating wound healing.
[0022] Specifically, the advantages are as follows:
[0023] (1) Possesses excellent mechanical properties. A porous drug-loaded nanofiber functional coating layer with a core-sheath structure is prepared using coaxial conjugate electrospinning technology to coat a biodegradable filament suture core layer with excellent mechanical properties. This gives the novel surgical suture with the core-spun yarn structure of the present invention excellent mechanical properties. Simultaneously, due to the addition of volatile oil, the drug-loaded nanofibers have uniform diameter, porous and rough surfaces, and a multi-layered, multi-dimensional interconnected pore structure, exhibiting a disordered aggregation state. This surface morphology effectively increases the surface friction of the fibers, improving the suture's fatigue resistance and friction tolerance, making the surgical suture less prone to slippage and retraction during use, thus enhancing its effectiveness.
[0024] (2) It possesses excellent biodegradability. The porous drug-loaded nanofiber functional coating layer with a core-skin structure prepared by coaxial conjugate electrospinning technology has good biodegradability in both the skin and core layers. At the same time, due to the addition of plant volatile oils, the electrospun nanofibers exhibit a high specific surface area and porous structure morphology, which can effectively enhance the degradation rate of the present invention, accelerate the biodegradation process of the suture, and enhance the performance of the suture.
[0025] (3) It possesses excellent drug controlled-release performance. The loaded drug is homogeneously distributed in the electrospinning precursor solution. After coaxial conjugate electrospinning, the drug is non-uniformly attached to the dermal structure of the suture wrapping layer in the form of granular spherical particles. As the dermal structure gradually degrades, the loaded drug is released synchronously to act on the cells and tissues at the suture site, reducing the number of administrations and maintaining a constant drug concentration in the blood. This achieves the purpose of continuous and effective controlled drug administration, thereby increasing the cumulative drug release rate and exhibiting excellent drug controlled-release effect, enhancing the effectiveness of the suture.
[0026] (4) Excellent healing-promoting properties. A porous drug-loaded nanofiber functional coating layer with a core-skin structure, prepared using coaxial conjugated electrospinning technology, incorporates core materials such as keratin and peptides to promote healing. As the core material gradually degrades, the core material is gradually exposed to exert its healing-promoting effect. The material itself possesses excellent biodegradability, biocompatibility, antibacterial properties, and cell-growth-promoting healing properties. For example, peptides are easily degraded, and their hydrolysis products are essential amino acids that can be absorbed by the human body; keratin is abundant, and its inherent ability to promote cell adhesion, proliferation, and tissue regeneration provides a biocompatible matrix for the regeneration and recovery of defective tissues. Simultaneously, the porous and rough structure of the nanofiber surface is beneficial for cell adhesion, growth, and differentiation, promoting tissue healing and enhancing the effectiveness of sutures.
[0027] (5) Excellent water retention properties. The porous drug-loaded nanofiber functional coating layer with a core-sheath structure, prepared using coaxial conjugate electrospinning technology, is composed of drug-loaded nanofiber bundles. The nanofibers have uniform diameter, high specific surface area, and high porosity, exhibiting a multi-layered and multi-dimensional structure and a disordered aggregation state. Their high specific surface area and high porosity can effectively improve the wetting of sutures and their effective contact with body fluids, enhance the water retention and liquid absorption of sutures, maintain tissue integrity, maintain the environment required for cell and tissue growth, and enhance the effectiveness of sutures.
[0028] (6) Possesses excellent antibacterial properties. The porous drug-loaded nanofiber functional coating layer with a core-sheath structure and a biodegradable core yarn layer with excellent mechanical properties, prepared by coaxial conjugated electrospinning technology, uses selected polymer raw materials such as polypeptides, keratin and polylactic acid, which all have certain antibacterial properties; the loaded drugs, such as amoxicillin, belong to the penicillin class of antibiotics, have broad-spectrum antibacterial properties, have strong bactericidal effects, can effectively inhibit bacterial growth at the wound site and induce wound tissue growth, reduce bacterial adhesion, promote healing, and enhance the effectiveness of sutures. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a schematic diagram of a coaxial conjugate electrospinning device. In the diagram, 1 is a coaxial electrospinning machine; 2 is an injection pump; 3 is a coaxial needle; 4 is a twisting device; 5 is an unwinding device; 6 is a winding device; and 7 is a core yarn.
[0031] Figure 2 This is a schematic diagram of the surgical suture structure of the present invention.
[0032] Figure 3 Figure 1 shows the in vitro degradation curves of surgical sutures. In Figure 2, curve a represents the test data of surgical sutures loaded with amoxicillin prepared in Examples 1-3, and curve b represents the test data of surgical sutures loaded with Bupleurum chinense prepared in Examples 4-6. In Figures a and b, 8% pPLA represents the test data of surgical sutures prepared in Comparative Example 1.
[0033] Figure 4 The figure shows the cumulative sustained-release curves of the simulated drug in vitro for surgical sutures. In the figure, curve a represents the test data of surgical sutures loaded with amoxicillin prepared in Examples 1-3, and curve b represents the test data of surgical sutures loaded with Bupleurum chinense prepared in Examples 4-6. Figure 5 This is a scanning electron microscope image of the surgical suture line containing the Western medicine amoxicillin in Example 1.
[0034] Figure 6 The figures show the mechanical properties of surgical sutures. In Figure a, the curve represents the test data of surgical sutures loaded with amoxicillin prepared in Examples 1-3, and the curve in Figure b represents the test data of surgical sutures loaded with Bupleurum chinense prepared in Examples 4-6. In Figures a and b, 8% pPLA represents the test data of surgical sutures prepared in Comparative Example 1.
[0035] Figure 7 The images show the antibacterial (Staphylococcus aureus) performance test results of surgical sutures, where a represents Example 1 containing amoxicillin and b represents Example 4 containing Bupleurum chinense.
[0036] Figure 8 The image shows a scanning electron microscope (SEM) image of the surgical suture line of Bupleurum chinense, a traditional Chinese medicine, in Example 4.
[0037] Figure 9 The figure shows the healing performance test curves of surgical sutures. In the figure, curve a represents the amoxicillin drug in Example 1, and curve b represents the Bupleurum chinense drug in Example 4.
[0038] Figure 10 This is a graph showing the water retention rate test data for surgical sutures. Detailed Implementation
[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] The coaxial conjugate electrospinning device used to prepare surgical sutures in the following embodiments has the following structure: Figure 1 As shown, the device includes a twisting device 4, an unwinding device 5, a winding device 6, and two symmetrically arranged coaxial electrospinning machines 1. The twisting device 4 is a funnel-shaped metal funnel that can rotate around its axis. The porous drug-loaded nanofiber functional encapsulation layer is twisted by rotating the metal funnel. The coaxial electrospinning machine 1 includes an injection pump 2 and a coaxial needle 3. The coaxial needle 3 is connected to a high-voltage DC power supply and forms a voltage difference (spinning voltage) between itself and the metal funnel. The spinning jet at the coaxial needle 3 is drawn and then received by the metal funnel. The core yarn 7 is wound on the unwinding device 5 and passes through the axis of the metal funnel and is fixed on the winding device 6. The surgical suture of the present invention can also be prepared using a device that combines it with an electrospinning machine to prepare core-spun yarn, such as the device for preparing electrospun nanofiber core-spun yarn disclosed in patents with publication numbers CN109554794A, CN109355715A, and CN104032423A, the difference being that the electrospinning machine is replaced with a coaxial electrospinning machine.
[0041] Example 1
[0042] A type of surgical suture, with the following structure: Figure 2 As shown, the suture consists of a porous drug-loaded nanofiber functional coating layer with a core-skin structure and a biodegradable core yarn support layer with excellent mechanical properties. Specifically, it achieves a rough surface structure with high water retention and liquid absorption, which is easy to degrade, provides sustained drug release, promotes healing, has excellent mechanical properties, increases friction, and prevents slippage, thus constructing a novel surgical suture.
[0043] A porous drug-loaded nanofiber functional coating layer with a core-skin structure was prepared using coaxial conjugated electrospinning technology. The nanofiber skin structure polymer raw material was polylactic acid (PLA), and the solvent was hexafluoroisopropanol. The mixture was magnetically stirred at 60°C to obtain an 8% (w / w) PLA spinning solution. Amoxicillin was selected as the loaded drug, and 1% (w / w) of amoxicillin relative to the PLA mass in the spinning solution was added. The mixture was magnetically stirred until the drug was fully dissolved and mixed in the spinning solution. Dodecylaldehyde, equivalent to 2% of the PLA mass, was added to the solution, and the mixture was magnetically stirred again until homogeneous to obtain the electrospinning precursor solution. The spinning voltage was 19±2 kV, the feed speed was 3 mL / h, the distance between the two needles was 25 cm, the receiving distance was 30 cm, the winding speed was 2 r / min, the twisting speed at the bell end was 300 r / min, the temperature was 20-25°C, and the relative humidity was approximately 50%. The core structure was made of zein-frog skin peptide, and the solvent was hexafluoroisopropanol at a concentration of 14 wt%. The mixture was magnetically stirred at room temperature for 2 h. The prepared amoxicillin-loaded sustained-release medical sutures were dried in a vacuum drying oven for 24 hours to remove residual solvent.
[0044] The biodegradable and mechanically strong core yarn support layer uses No. 0 polylactic acid suture, which mainly provides the necessary mechanical support.
[0045] Example 2
[0046] A new type of surgical suture, with a structure as follows Figure 2 As shown, the suture consists of a porous drug-loaded nanofiber functional coating layer with a core-skin structure and a biodegradable core yarn support layer with excellent mechanical properties. Specifically, it achieves a rough surface structure with high water retention and liquid absorption, which is easy to degrade, provides sustained drug release, promotes healing, has excellent mechanical properties, increases friction, and prevents slippage, thus constructing a novel surgical suture.
[0047] A porous drug-loaded nanofiber functional coating layer with a core-skin structure was prepared using coaxial conjugated electrospinning technology. The polymer raw material for the nanofiber skin structure was polylactic acid, and the solvent was hexafluoroisopropanol. The solution was prepared by magnetic stirring at 60°C to obtain a 9% (w / w) polylactic acid spinning solution. The drug loaded was amoxicillin. Amoxicillin was added at 1.5% (w / w) of the mass of polylactic acid in the spinning solution. The solution was magnetically stirred until the drug was fully dissolved and mixed in the spinning solution. 4-terpineol was added to the solution at 1% (w / w) of the amount of polylactic acid added. The solution was magnetically stirred again until it was uniformly mixed to obtain the electrospinning precursor solution. The spinning voltage was 21±2kV, the feed speed was 3mL / h, the distance between the two needles was 25cm, the receiving distance was 32cm, the winding speed was 3r / min, the twisting speed at the bell mouth was 400r / min, the temperature was 20-25℃, and the relative humidity was around 50%. The core layer structure was made of keratin, the solvent was deionized water with a concentration of 10wt%, and the mixture was magnetically stirred at room temperature for 30min. The prepared amoxicillin-loaded sustained-release medical suture was then dried in a vacuum drying oven for 36h to remove residual solvent.
[0048] The biodegradable and mechanically strong core yarn support layer uses No. 0 polylactic acid suture, which mainly provides the necessary mechanical support.
[0049] Example 3
[0050] A new type of surgical suture, with a structure as follows Figure 2 As shown, the suture consists of a porous drug-loaded nanofiber functional coating layer with a core-skin structure and a biodegradable core yarn support layer with excellent mechanical properties. Specifically, it achieves a rough surface structure with high water retention and liquid absorption, which is easy to degrade, provides sustained drug release, promotes healing, has excellent mechanical properties, increases friction, and prevents slippage, thus constructing a novel surgical suture.
[0051] A porous drug-loaded nanofiber functional coating layer with a core-skin structure was prepared using coaxial conjugated electrospinning technology. The nanofiber skin structure polymer raw material was polylactic acid (PLA), and the solvent was hexafluoroisopropanol. The mixture was magnetically stirred at 60°C to obtain an 8% (w / w) PLA spinning solution. Amoxicillin was selected as the loaded drug, and 2% (w / w) of amoxicillin was added relative to the PLA mass in the spinning solution. The mixture was magnetically stirred until the drug was fully dissolved and mixed in the spinning solution. Dodecylaldehyde, equivalent to 3% of the PLA mass, was added to the solution, and the mixture was magnetically stirred again until homogeneous to obtain the electrospinning precursor solution. The spinning voltage was 23±2 kV, the feed speed was 3 mL / h, the distance between the two needles was 27 cm, the receiving distance was 32 cm, the winding speed was 4 r / min, the twisting speed at the bell end was 400 r / min, the temperature was 20-25°C, and the relative humidity was approximately 50%. The core structure was made of zein-frog skin peptide, and the solvent was hexafluoroisopropanol at a concentration of 14 wt%. The mixture was magnetically stirred at room temperature for 2 h. The prepared amoxicillin-loaded sustained-release medical sutures were dried in a vacuum drying oven for 48 hours to remove residual solvent.
[0052] The biodegradable and mechanically strong core yarn support layer uses No. 0 polylactic acid suture, which mainly provides the necessary mechanical support.
[0053] Example 4
[0054] A new type of surgical suture, with a structure as follows Figure 2 As shown, the suture consists of a porous drug-loaded nanofiber functional coating layer with a core-skin structure and a biodegradable core yarn support layer with excellent mechanical properties. Specifically, it achieves a rough surface structure with high water retention and liquid absorption, which is easy to degrade, provides sustained drug release, promotes healing, has excellent mechanical properties, increases friction, and prevents slippage, thus constructing a novel surgical suture.
[0055] A porous drug-loaded nanofiber functional wrapping layer with a sheath-core structure is prepared by coaxial conjugate electrostatic spinning technology. The polymer raw material for the nanofiber sheath structure is polylactic acid, the solvent is hexafluoroisopropanol, and the mixture is magnetically stirred at a constant temperature of 60℃ to prepare a polylactic acid spinning dope with a mass fraction of 8%. The loaded drug is Bupleuri Radix, which is added in an amount of 1% relative to the mass of polylactic acid in the spinning dope, and magnetically stirred until the drug is fully dissolved and mixed in the spinning solution to obtain a uniformly mixed electrostatic spinning precursor solution. The spinning voltage is 19±2kV, the propulsion speed is 3mL / h, the distance between the two needles is 25cm, the receiving distance is 30cm, the winding speed is 2r / min, the trumpet twisting speed is 300r / min, the temperature is 20-25℃, and the relative humidity is about 50%; the core layer structure uses zein-Rana chensinensis skin polypeptide, the solvent is hexafluoroisopropanol, the concentration is 14wt%, and the mixture is magnetically stirred at room temperature for 2h. The prepared Bupleuri Radix-loaded sustained-release medical suture is placed in a vacuum drying oven for 24h to remove residual solvent.
[0056] The biodegradable core yarn support layer with excellent mechanical properties uses No. 0 polylactic acid-based suture, which mainly provides necessary mechanical property support.
[0057] Example 5
[0058] A novel surgical suture, with the structure as shown in Figure 2 , is composed of a porous drug-loaded nanofiber functional wrapping layer with a sheath-core structure and a biodegradable core yarn support layer with excellent mechanical properties, which specifically realizes a rough specific surface structure with high water retention and liquid absorbency that is easy to degrade, enables sustained drug release, promotes healing, has excellent mechanical properties, increases friction, and prevents slippage, so as to construct the novel surgical suture.
[0059] A porous drug-loaded nanofiber functional wrapping layer with a sheath-core structure is prepared by coaxial conjugate electrostatic spinning technology. The polymer raw material for the nanofiber sheath structure is polylactic acid, the solvent is hexafluoroisopropanol, and the mixture is magnetically stirred at a constant temperature of 60℃ to prepare a polylactic acid spinning dope with a mass fraction of 9%. The loaded drug is Bupleuri Radix, which is added in an amount of 2% relative to the mass of polylactic acid in the spinning dope, and magnetically stirred until the drug is fully dissolved and mixed in the spinning solution to obtain a uniformly mixed electrostatic spinning precursor solution. The spinning voltage is 21±2kV, the propulsion speed is 3mL / h, the distance between the two needles is 26cm, the receiving distance is 32cm, the winding speed is 3r / min, the trumpet twisting speed is 300r / min, the temperature is 20-25℃, and the relative humidity is about 50%; the core layer structure uses zein-Rana chensinensis skin polypeptide, the solvent is hexafluoroisopropanol, the concentration is 14%, and the mixture is magnetically stirred at room temperature for 2h. The core layer structure uses keratin, the solvent is deionized water, the concentration is 10wt%, and the mixture is magnetically stirred at room temperature for 30min. The prepared Bupleuri Radix-loaded sustained-release medical suture is placed in a vacuum drying oven for 36h to remove residual solvent.
[0060] The core yarn support layer with biodegradability and excellent mechanical properties is selected as No. 0 polylactic acid-type suture, which mainly provides necessary mechanical property support.
[0061] Example 6
[0062] A novel surgical suture has a structure as shown in Figure 2 , which consists of a porous drug-loaded nanofiber functional wrapping layer with a sheath-core structure and a core yarn support layer with biodegradability and excellent mechanical properties. Specifically, it realizes a rough specific surface structure with high water retention and liquid absorbency that is easily degradable, can achieve sustained drug release, promotes healing, has excellent mechanical properties, increases friction and prevents slipping, so as to construct the novel surgical suture.
[0063] The porous drug-loaded nanofiber functional wrapping layer with a sheath-core structure is prepared by coaxial conjugate electrostatic spinning technology. For the polymer raw material of the nanofiber sheath structure, polylactic acid is selected, and hexafluoroisopropanol is selected as the solvent. The mixture is magnetically stirred at a constant temperature of 60°C to prepare a polylactic acid spinning dope with a mass fraction of 8%. Bupleurum is selected as the loaded drug, and Bupleurum accounting for 3% of the mass of polylactic acid in the spinning dope is added, followed by magnetic stirring until the drug is fully dissolved and mixed in the spinning solution, so as to obtain a uniformly mixed electrostatic spinning precursor solution. The spinning voltage is 23±2kV, the propulsion speed is 3mL / h, the distance between the two needles is 27cm, the receiving distance is 32cm, the winding speed is 4r / min, the twisting speed of the bell mouth is 400r / min, the temperature is 20-25°C, and the relative humidity is about 50%. For the core layer structure, zein-forest frog skin polypeptide is selected, hexafluoroisopropanol is selected as the solvent, the concentration is 14wt%, and magnetic stirring is carried out at room temperature for 2h. The prepared Bupleurum-loaded sustained-release medical suture is placed in a vacuum drying oven for 48 hours to remove residual solvent.
[0064] The core yarn support layer with biodegradability and excellent mechanical properties is selected as No. 0 polylactic acid-type suture, which mainly provides necessary mechanical property support.
[0065] Example 7
[0066] A surgical suture has a structure as shown in Figure 2 , which includes a porous drug-loaded nanofiber functional wrapping layer and a core yarn support layer. The porous drug-loaded nanofiber functional wrapping layer comprises nanofibers with a sheath-core structure, and the nanofibers with a sheath-core structure include a drug-loaded sheath layer and a biological material core layer.
[0067] A porous drug-loaded nanofiber functional coating layer with a core-skin structure was prepared using coaxial conjugated electrospinning technology. The nanofiber skin structure polymer raw material was polylactic acid (PLA), and the solvent was chloroform. A 5% (w / w) PLA spinning solution was prepared by magnetic stirring at 60°C. The loaded drug was an antibiotic; 1% (w / w) of antibiotic relative to the PLA mass in the spinning solution was added, and the mixture was magnetically stirred until the drug was fully dissolved and mixed in the spinning solution. Then, 1% (w / w) of 4-terpineol (equivalent to the amount of PLA) was added to the solution, and the mixture was magnetically stirred again until homogeneous to obtain the electrospinning precursor solution. The spinning conditions were: spinning voltage 28 kV, feed speed 5 mL / h, needle distance 30 cm, receiving distance 35 cm, winding speed 5 r / min, flared twist speed 400 r / min, temperature 20-25°C, and relative humidity around 60%. The core structure was made of zein-frog skin peptide, and the solvent was chloroform at a concentration of 20 wt%. The mixture was magnetically stirred at room temperature for 2 h. The prepared antibiotic-loaded sustained-release medical sutures were dried in a vacuum drying oven for 12 hours to remove residual solvent.
[0068] The biodegradable and mechanically strong core yarn support layer uses polydioxanone sutures, which mainly provide the necessary mechanical support.
[0069] Example 8
[0070] A type of surgical suture, with the following structure: Figure 2 As shown, it includes a porous drug-loaded nanofiber functional coating layer and a core yarn support layer. The porous drug-loaded nanofiber functional coating layer includes core-shell structured nanofibers, which include a drug-loaded skin layer and a biomaterial core layer.
[0071] A porous drug-loaded nanofiber functional coating layer with a core-skin structure was prepared using coaxial conjugated electrospinning technology. The nanofiber skin structure polymer raw material was polylactic acid (PLA), and the solvent was acetone. A 15% (w / w) PLA spinning solution was prepared by magnetic stirring at 60°C. Vitamins were selected as the loaded drug, and 1% (w / w) of vitamins relative to the PLA mass in the spinning solution was added. Magnetic stirring continued until the drug was fully dissolved and mixed in the spinning solution. Dodecylaldehyde, equivalent to 1% of the PLA mass, was added to the solution, and the mixture was stirred again until homogeneous to obtain the electrospinning precursor solution. The spinning conditions were: spinning voltage 22±2 kV, feed speed 1 mL / h, needle distance 20 cm, receiving distance 20 cm, winding speed 3 r / min, flared twisting speed 200 r / min, temperature 20-25°C, and relative humidity around 30%. The core structure was made of zein-frog skin polypeptide, and vitamins were used as the solvent at a concentration of 10 wt%. The mixture was magnetically stirred at room temperature for 2 h. The prepared vitamin-loaded sustained-release medical sutures were dried in a vacuum drying oven for 24 hours to remove residual solvents.
[0072] The biodegradable and mechanically strong core yarn support layer uses No. 0 polylactic acid suture, which mainly provides the necessary mechanical support.
[0073] Comparative Example 1
[0074] Nano-polylactic acid (PLA) fibers were prepared using electrospinning technology with hexafluoroisopropanol as the solvent. The mixture was magnetically stirred at a constant temperature of 60°C to obtain an 8% (w / w) PLA spinning solution. Then, 3% (w / w) of Bupleurum chinense (Radix Bupleuri) relative to the PLA mass in the spinning solution was added. The mixture was magnetically stirred until the drug was fully dissolved and mixed in the spinning solution. The spinning voltage was 19±2 kV, the feed speed was 3 mL / h, the distance between the two needles was 25 cm, the receiving distance was 30 cm, the winding speed was 3 r / min, the flared twisting speed was 400 r / min, the temperature was 20-25°C, and the relative humidity was around 50%. The prepared Bupleurum-loaded sutures were dried in a vacuum drying oven for 48 h to remove residual solvent.
[0075] Performance testing
[0076] The samples from Examples 1-6 and Comparative Example 1 were subjected to relevant performance tests, including in vitro degradation rate, drug sustained release effect, healing promotion effect, mechanical properties, antibacterial effect, etc. For some specific test requirements, please refer to the standard "YY1116-2020 Absorbable Surgical Sutures".
[0077] Test 1
[0078] The surgical sutures underwent in vitro degradation performance testing, and the test results are as follows: Figure 3 As shown. Buffer solution preparation: Weigh 0.24 g of potassium dihydrogen phosphate, 1.44 g of disodium hydrogen phosphate, 8.0 g of sodium chloride, and 0.2 g of potassium chloride, add them to a beaker containing 800 mL of deionized water, stir thoroughly, then add a trace amount of concentrated hydrochloric acid to titrate to pH 7.4, and finally bring the buffer solution to a final volume of 1 L. Precisely measure the coated sutures using a precision electronic balance, weighing 8 portions and recording the weight, then placing the samples into the prepared buffer solution. Periodically (1 day, 2 days, 3 days, 4 days, 5 days, 6 days, 7 days, 10 days), remove the fibers from the PBS buffer solution, dry them thoroughly in an electric heating oven at 30°C, and then weigh them to calculate the weight loss rate. The in vitro degradation rate is better than that of unloaded nanofibers, which is related to the irregular porous surface structure of the sutures prepared by coaxial conjugate electrospinning technology, indicating that the prepared sutures have excellent degradability.
[0079] Test 2
[0080] The surgical sutures underwent in vitro simulated drug release performance testing, and the test results are as follows: Figure 4As shown. Drug-loaded surgical sutures (0.05 g) were immersed in PBS buffer (10 mL) with pH 5.5 and pH 7.5, respectively, and placed in a 37.5℃ incubator for drug release. At time points of 0.5, 1, 1.5, 2, 4, 8, 16, 32, 48, 72, 90, and 144 hours, 1 mL of the released solution was collected, and 1 mL of buffer solution at 37.5℃ was added simultaneously. The absorbance of the release medium at 283 nm was measured using a UV-1100 ultraviolet spectrophotometer, and the cumulative drug release was calculated. It can be seen that the drug concentration has little effect on the sustained-release rate and stages, but it does affect the cumulative percentage of drug release; the higher the drug loading concentration, the higher the cumulative percentage of drug release. Furthermore, from... Figure 4 a and Figure 4 b. It can be observed that both the PLA-loaded Western medicine sustained-release and the Bupleurum-loaded traditional Chinese medicine sustained-release are clearly divided into three stages. In the first stage, the release rates of both amoxicillin and Bupleurum are relatively fast within 4 hours. At 4 hours, the release concentrations of amoxicillin are 14.3% (1% loaded), 16.2% (1.5% loaded), and 17.1% (2% loaded), respectively, while the release concentrations of Bupleurum are 17.6% (1% loaded), 16.0% (2% loaded), and 17.3% (3% loaded), respectively. In the second stage, from 4 to 72 hours, the release rates of both amoxicillin and Bupleurum decrease, but the release rate of Bupleurum is faster than that of amoxicillin. Both maintain a certain linear cumulative release rate. In the third stage, after 72 hours, the release rates of both amoxicillin and Bupleurum chinense tended to plateau. The cumulative release percentages of amoxicillin were 82.8% (1% drug loading), 85.4% (1.5% drug loading), and 88.3% (2% drug loading), respectively, while the cumulative release percentage of Bupleurum chinense reached a stable peak of 75.5% (1% drug loading), 77.5% (2% drug loading), and 77.6% (3% drug loading), respectively. Because the surface porosity of the sutures loaded with amoxicillin was lower than that loaded with Bupleurum chinense, the initial drug release rate was slower for amoxicillin than for Bupleurum chinense. In addition, because the dosage of Bupleurum chinense was larger than that of amoxicillin, the cumulative release percentage of the pharmacologically active components of Bupleurum chinense was lower than that of amoxicillin when the drug loading concentrations were similar. Therefore, when the final cumulative release percentage reached a stable peak, the cumulative release percentage of Bupleurum chinense was lower than that of amoxicillin.
[0081] The surgical sutures prepared in Example 1 were subjected to scanning electron microscopy, and the test results are as follows: Figure 5 As shown, a distinct core-spun yarn structure is visible. Due to the addition of volatile oil, the surface of the nanofibers exhibits a clearly irregular porous structure, with distinctly rough, granular, non-uniformly attached particles, which are the loaded drug amoxicillin.
[0082] Test 3
[0083] The mechanical properties of the surgical sutures were tested, and the test results are as follows: Figure 6As shown. According to the standard "YY1116-2020 Absorbable Surgical Sutures," which specifies the testing standards and requirements for the breaking strength of sutures, a simple knot is tied in the middle of the suture, the knot is tightened, and both ends of the suture are fixed to two clamps on a material testing machine, with the knot positioned in the middle of the clamps. The suture is then pulled taut at a specified speed, and the maximum tensile force is recorded as the single-strand breaking strength value. If the suture breaks within 1 cm of the clamp, the data is discarded. The average value of all single-strand values is calculated as the average breaking strength. The suture of this invention, tested according to standard requirements, exhibits a knot breaking strength far exceeding the standard, demonstrating excellent mechanical properties and meeting the mechanical requirements of national standards and ideal sutures.
[0084] Test 4
[0085] The antibacterial properties of the surgical sutures were tested, and the test results are as follows: Figure 7 As shown. After preparing the necessary conditions for the antibacterial experiment, proceed with the experiment. Before the experiment, disinfect with alcohol to ensure a sterile environment throughout. Open the prepared solid culture medium and place it upright. Use a pipette to take 50 μL of the solid culture medium and then spread it evenly with a spreader. Repeat this process for each product. After completion, place the prepared solid culture medium in a shaker and incubate at 37°C for 12 hours. Observe the experimental phenomena. The antibacterial effect becomes more pronounced with increasing drug concentration.
[0086] The surgical sutures prepared in Example 4 were subjected to scanning electron microscopy, and the test results are as follows: Figure 8 As shown, a distinct core-spun yarn structure is visible. Due to the addition of volatile oil, the surface of the nanofibers exhibits a clearly irregular porous structure with distinctly rough, granular, non-uniformly attached particles, which are the loaded drug, Bupleurum chinense. Furthermore, it should be noted that the Bupleurum chinense used in this invention contains saponins, polysaccharides, volatile oils, and other major chemical components. Therefore, in addition to its analgesic, antibacterial, and anti-inflammatory pharmacological effects, its main active ingredient, volatile oil, also acts as an additive in this invention to achieve pore-forming properties.
[0087] Test 5
[0088] The healing-promoting properties of surgical sutures were tested, and the test results are as follows: Figure 9 As shown. Using the MTT assay: cells were routinely digested, centrifuged to collect the cell pellet, resuspended in serum-containing complete culture medium to prepare a cell suspension, cell counting was performed, and the cell concentration was diluted to 1x10⁻⁶. 4Cells / ml. Using a pipette, 200 μL of the diluted cell suspension was added to a 96-well plate and cultured at 37°C with 5% CO2. The medium was changed every 2-3 days. Starting from the second day of cell culture, the 96-well plate was removed daily at a fixed time, and 20 μL of MTT solution was added. After incubation at 37°C for 4 hours, the supernatant was carefully aspirated from each well, and 150 μL of DMSO was added to each well. The plate was shaken for 10 minutes to fully dissolve the precipitate. The absorbance was measured at 490 nm using a microplate reader, and the results were recorded. Cells were observed to gradually grow, indicating that the suture of this invention has a certain healing-promoting effect.
[0089] Test 6
[0090] The water retention properties of the surgical sutures were tested, and the test results are as follows: Figure 10 As shown in the figure, the amoxicillin-loaded Western medicine corresponds to Examples 1-3, and the Bupleurum-loaded traditional Chinese medicine corresponds to Examples 4-6. Wound healing dressings need to have a certain water retention capacity to maintain a moist environment on the wound surface. Based on the data in the figure, the water retention capacity of the novel surgical suture of this invention is superior to that of Comparative Example 1. According to scanning electron microscopy analysis, this is mainly due to the irregular porous structure of the fiber surface, which improves the water retention and absorption performance of the suture.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing surgical sutures, comprising using an apparatus for preparing electrospun nanofiber core-spun yarns, characterized in that, The surgical suture includes a porous drug-loaded nanofiber functional wrapping layer and a core yarn support layer. The porous drug-loaded nanofiber functional wrapping layer includes core-skin structured nanofibers, which include a drug-loaded skin layer and a biomaterial core layer. The device for preparing electrospun nanofiber core-spun yarn includes a coaxial electrospinning machine. The preparation method is as follows: (1) mixing the polymer and the drug to prepare a skin layer spinning solution; (2) dissolving the biomaterial to prepare a core layer spinning solution; (3) obtaining core-skin structured nanofibers from the skin layer spinning solution and the core layer spinning solution through a coaxial electrospinning machine, and wrapping them on the core yarn. In step (1), a pore-forming agent is also added to the skin layer spinning solution. The amount of the pore-forming agent added is 1-3% of the polymer mass. The pore-forming agent is a volatile oil. The volatile oil is 4-terpineol and dodecylaldehyde. The polymer is polylactic acid; the drug is one or more of antibiotics, anti-inflammatory drugs, hemostatic drugs, or vitamins; the biomaterial is one or more of keratin, gelatin, silk protein, collagen, chitosan, or polypeptides; and the core yarn is one or more of polyglycolic acid, polylactic acid, or polydioxanone sutures.
2. The method for preparing surgical sutures according to claim 1, characterized in that, The concentration of polymer in the skin spinning solution is 5-15 wt%; the amount of drug added is 1-3% of the polymer mass.
3. The method for preparing surgical sutures according to claim 2, characterized in that, The solvent of the skin spinning solution is one or more of hexafluoroisopropanol, chloroform, or acetone.
4. The method for preparing surgical sutures according to claim 1, characterized in that, The drug in question is either amoxicillin or Bupleurum chinense.
5. The method for preparing surgical sutures according to claim 1, characterized in that, The concentration of biomaterial in the core spinning solution is 10-20 wt%.
6. The method for preparing surgical sutures according to claim 1, characterized in that, The solvent for the core spinning solution is one or more of hexafluoroisopropanol, chloroform, or acetone.
7. The method for preparing surgical sutures according to claim 1, characterized in that, The apparatus for preparing electrospun nanofiber core-spun yarn is a coaxial conjugate electrospinning apparatus. The coaxial conjugate electrospinning apparatus further includes a twisting device, an unwinding device, and a winding device. It is equipped with two coaxial electrospinning machines arranged symmetrically. The technical parameters for preparing surgical sutures using the coaxial conjugate electrospinning apparatus are as follows: voltage 18-28kV, solution propulsion speed 1-5mL / h, distance between two needles 20-30cm, receiving distance 20-35cm, winding device rotation speed 2-5r / min, and twisting device rotation speed 200-400r / min.
Citation Information
Patent Citations
Nano-fiber covering yarn electrostatic spinning device and application thereof
CN104032423A
Preparing method of medicine-carrying nanofiber core spun yarn for absorbable surgical suture
CN108193342A
Stretchable multi-mode sensor based on nanofiber core spun yarn and preparation method thereof
CN109355715A
Yarn forming device and method for electrospinning nanofiber core-spun yarns
CN109554794A
Drug-loading suture adopting core-shell composite structure and preparation method of drug-loading suture
CN106075544A